Applications of graphene and its derivatives as an adsorbent for heavy metal and dye removal: a systematic and comprehensive overview. Issue 62 (8th July 2015) - Yusuf, Mohammed; Elfghi, F. M.; Zaidi, Shabi Abbas; Abdullah, E. C.; Khan, Moonis Ali
<x xml:space="preserve">Abstract</x> Because of their persistency and toxicity, dyes and heavy metal ions discharged to water bodies have become a worrisome issue.